Study Habits and Academic Performance of Biology Students Amid Blended Learning Experience - Onipede, Joy Abiola; Adeniji , Ajibola Abidemi; Edegbai, Asepeoreoluwa Blessing; Liadi, Adewale Ismaheel; Tijani, Olaitan Noheemat; Asuni, Soburat Olayemi (Universitas Lancang Kuning, 2025)
The prominence gained by blended learning educational approach has led to its rapid adoption within educational setting with several scholars and studies establishing the significance of blended learning approach to quality academic performance. The current study delves into the influence of blended learning on study habits and academic performance of biology student in Abeokuta South Local Government Area, Ogun state of Nigeria. To achieve the objectives of the study, 250 respondents were sampled. The selection of students aligns with the descriptive research design of the study as the students were selected from 10 senior secondary Schools in the study Area. The data collected were summarized into tables and analyzed using descriptive statistics while Pearson Moment correlation coefficient, and a linear regression at 0.05 level of significance were utilized to test the hypothesis of the study. The results of the study indicate a 65.8% variance in students’ performance in Biology amidst blended learning with the improvement showcasing the extent at which study habit improves student academic performance (F (1, 248) =19.46, p = 0.001). No significance difference was found to exist between gender in terms of their study habit (t (248) = 1.819, at P>0.05). A significant difference was observed between the study habit of Students from Private and Public secondary schools t (248) = 4.131, at P<0.05. We recommend that educators and policymakers should work together in creating study habits and academic performance. a supportive learning environment, like blended learning approach which would help improve students